2017
DOI: 10.1111/cbdd.12981
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, biological evaluation, and molecular docking of novel flavones as H3R inhibitors

Abstract: A series of novel flavone derivatives were designed, synthesized, and evaluated for their H R inhibitory activity. The results showed that four compounds exhibited significant anti-H R activity. Molecular docking experiments indicated that a salt bridge, hydrogen-bonding, and hydrophobic interactions all contributed to interactions between inhibitors and H R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
(39 reference statements)
1
10
0
Order By: Relevance
“…The results of docking indicate that the critical amino acids interacting with different parts of selected molecules are as follows: Glu 206 (TM5) in the interaction with basic moiety, Tyr 115 (TM3) and Tyr 374 (TM6) residues interact with linker, and Tyr 189 (TM5) and Phe 398 (TM7) forms the hydrophobic pocket with hydrophobic/aromatic moiety ( Figure S3.1). These findings are in close agreement with the findings published previously (Axe et al, 2006;Bajda et al, 2012;Harusawa et al, 2013;Kuder et al, 2016;Łażewska et al, 2016;Lepailleur et al, 2014;Levoin et al, 2013;Morini et al, 2006;Sheng et al, 2015;Wen et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of docking indicate that the critical amino acids interacting with different parts of selected molecules are as follows: Glu 206 (TM5) in the interaction with basic moiety, Tyr 115 (TM3) and Tyr 374 (TM6) residues interact with linker, and Tyr 189 (TM5) and Phe 398 (TM7) forms the hydrophobic pocket with hydrophobic/aromatic moiety ( Figure S3.1). These findings are in close agreement with the findings published previously (Axe et al, 2006;Bajda et al, 2012;Harusawa et al, 2013;Kuder et al, 2016;Łażewska et al, 2016;Lepailleur et al, 2014;Levoin et al, 2013;Morini et al, 2006;Sheng et al, 2015;Wen et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…By solving the 3D structure of bovine rhodopsin using crystallography technique in 2000, this protein was used for modeling of GPCRs as the only available template for several years as well as for H 3 R. Following the introduction of crystal structure for histamine H 1 receptor in complex with doxepin by Shimamura et al. (), it was used for developing more realistic homology models for H 3 R in comparison with bovine rhodopsin (Harusawa et al., ; Tang et al., ; Wen, Liu, Hu, Wang, & Wu, ). However, the structural features can be considered in addition to sequence similarity for alignment of target and template sequence for modeling purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavone and iso-flavone, which are regarded as privileged structures, exhibit variety of pharmacological activities, such as anti-cancer, antimicrobial, anti-inflammatory, and also are used in neurodegenerative disorders, for example, Alzheimer’s disease 22–24 . Our previous study had confirmed the iso-flavone and flavone compounds possessed moderate inhibitory activity against H 3 R 25 . Particularly, the optimization at the 8-position of the flavones and 7-position of iso-flavone provided satisfactory bioactivity (compound A , B, and C , Figure 1 ), which enlightened us to modify 8-position of iso-flavone to enhance the H 3 R inhibitory effect.…”
Section: Introductionmentioning
confidence: 77%
“…We chose the most active compounds for molecular docking studies to predict how molecules and proteins work. A homology modelling of H 3 R was built as our previous report 25 . The 3D structure of compound 2h was built using DS MODELER (Discovery Studio 2016, BIOVIA Inc, San Diego, CA) and evaluated the model according to the PDF Total Energy and the Profile-3D procedure.…”
Section: Bioassay Studiesmentioning
confidence: 99%